Predicting Shame and Guilt Based on Self-differentiation and Defense Mechanisms - Maryam Rajabpour; Banafsheh Omidvar (Iranian Evolutionary Educational Psychology Journal, 2020)
The purpose of this study was to predict shame and guilt based on self-differentiation and defense mechanisms. The research method is correlation. The statistical population of this study was students of Islamic Azad University of Pardis branch of Shiraz. Random cluster sampling method was used to select 140 people as the sample group. Participants responded to Self-Conscious Affect Inventory, Self-Differentiation (short form) Scale, and Self-Defense Styles inventory. Data were analyzed using multiple regression analysis with SPSS software. Findings showed that dimension of self-differentiation was a negative and significant predictor of feeling shame. In addition, the results showed that underdeveloped defense mechanisms were negative and significant predictors of guilt, and underdeveloped and psychosomatic defense mechanisms were positive and significant predictors of shame. Overall, it can be concluded that the effect of defense mechanisms and their differentiation dimensions on the sense of shame and guilt is important.